Pathophysiology, Management, and Therapeutics in Subarachnoid Hemorrhage and Delayed Cerebral Ischemia: An Overview - Henry W. Sanicola; Caleb E. Stewart; Patrick Luther; Kevin Yabut; Bharat Guthikonda; J. Dedrick Jordan; J. Steven Alexander (Pathophysiology, 2023)
Subarachnoid hemorrhage (SAH) is a type of hemorrhagic stroke resulting from the rupture of an arterial vessel within the brain. Unlike other stroke types, SAH affects both young adults (mid-40s) and the geriatric population. Patients with SAH often experience significant neurological deficits, leading to a substantial societal burden in terms of lost potential years of life. This review provides a comprehensive overview of SAH, examining its development across different stages (early, intermediate, and late) and highlighting the pathophysiological and pathohistological processes specific to each phase. The clinical management of SAH is also explored, focusing on tailored treatments and interventions to address the unique pathological changes that occur during each stage. Additionally, the paper reviews current treatment modalities and pharmacological interventions based on the evolving guidelines provided by the American Heart Association (AHA). Recent advances in our understanding of SAH will facilitate clinicians’ improved management of SAH to reduce the incidence of delayed cerebral ischemia in patients.